The Relationship Between Directors' Transformational Leadership Behaviors and Subordinates' Organizational Commitment at the National Sports Council - Kok, Mong Lin (2005)
This research sought to examine the correlation between directors' transformational leadership behaviors and subordinates' organizational commitment at the National Sports Council of Malaysia. Data were collected from 150 proportional stratified samples. Two instruments were used: 1) the Transformational Leadership Inventory (TLI) developed by Podsakoff, MacKenzie, Moorman and Fetter (1990) measuring employees' perception of transformational leadership behaviors of their divisional directors; 2) the Organizational Commitment Questionnaire (OCQ) developed by Mowday, Porter, and Steers (1979) to measure employees' organizational commitment. The research design used is of descriptive correlational type. Data collected were analyzed using descriptive statistics, Pearson correlation, t-tests, stepwise multiple regression, and ANOVA. The relationship between directors' transformational leadership behaviors and subordinates' organizational commitment was found to be strong and positively significant. Male perceived higher level of commitment than female workers. Demographic factors such as gender and educational status contributed significantly to organizational commitment, with educational status being the best predictor of the outcome variable. Significant difference was found in the perceptions of transformational leadership behaviors and organizational commitment among the six divisions in NSC. Significant gender difference was also noted in the perceptions of transformational leadership behaviors. It is hoped that the findings of this study will contribute towards the wider knowledge of this leadership paradigm, and more practical application and manifestation of this leadership in various organizations in this changing world of globalization. Possible instrument limitations and future research needs are also reviewed.